The Impact of Using Skimming and Scanning Strategies of Descriptive Text Towards Students’ Reading Comprehension at Grade Eight of Smpn 22 Bandar Lampung - Yuli Fatmawati (International Conference on Education and Language (ICEL), 2014)
The objective of this research was to find out the impact of using skimming and scanning strategies towards the students’ reading comprehension at grade eight of SMPN 22 Bandar Lampung.Reading comprehension refers to the readers’ ability to understand the information of reading text. The use of skimming and scanning strategies in teaching reading is expected to be able to improve the students’ reading comprehension.Data collection was administered by conducting two pre-test and two post-test in experimental group and control group. Treatment was administered for experimental group by using skimming and scanning strategies. While control group was treated by using traditional teaching.Data analysis was attempted by using t-Test for two group design. Results indicated that p-value 1% = 2.68, 5% = 2.01, and t-value = 14,882. It is statistically significant as p-value is smaller than t-value. Therefore, null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted.These findings suggest that there is impact of using skimming and scanning strategies towards the students’ reading comprehension at grade eight of SMPN 22 Bandar Lampung. It is suggested that the teacher uses skimming and scanning strategies for teaching reading.